A verbo-visualidade na obra de Deivid Pereira - Borges, Margarida Rodrigues de Andrade (2023)
This dissertation discusses a verb-visual analysis in the artistic work produced and adapted by the Deaf artist Deivid Pereira. This production was created and adapted for Deaf culture because it includes the presence of visual resources of written texts in Libras through the SignWriting system - SW for the writing of Sign Languages. His productions are illustrations that carry verbal and non-verbal language in their design, promoting visual communication. Our theoretical framework is based on Bakhtin and his Circle in dealing with theoretical categories: the notion of authorship, the audience, meaning, ideology, signs, aesthetics, style, polyphony, and particularly the verb-visuality of Brait (2009; 2013). Our general objective is to describe, based on meaning, the structural and "content" issues of the verb-visuality contained in Deivid Pereira's work. And our specific objectives are: to discuss the relationship between Deaf culture, identity, and verb-visuality; to analyze the existing dialogical relationships in the illustrations; to investigate the relationship of verb-visual meaning in Deivid Pereira's work and identify how verbal text is presented in the text that constitutes itself as verb-visual text. To do this, we intend to find an answer to the following question: What are the effects of meaning in the verb-visual text of Deivid Pereira's work? To answer this question, we propose to analyze three works that address relevant social issues such as violence against women, sugarcane cutting work, and racism. We adopt a qualitative methodology of a documentary nature and technique to analyze the production of meaning in the verb-visual text of the aforementioned works. The data confirm that the analyzed works are texts belonging to the verb-visual category and highlight the ideologies and values of Deaf culture. In the results of the analysis, we emphasize the category of meaning, as well as other analytical categories derived from Bakhtin's thought. Due to the circulation of artistic productions in different spaces, whether physical or digital, in the signed or written mode of Libras, as is the case with the works analyzed here, we emphasize that the artistic creations of Deaf individuals highlight their Deaf culture through visual experiences in sign language, which encourages the emergence of new forms of artistic beauty.